Lung size and liver herniation predict need for extracorporeal membrane oxygenation but not pulmonary hypertension in isolated congenital diaphragmatic hernia: systematic review and meta‐analysis. (26th April 2017) - Russo, F. M.; Eastwood, M. P.; Keijzer, R.; Al‐Maary, J.; Toelen, J.; Van Mieghem, T.; Deprest, J. A.
ABSTRACT: Objectives: To identify antenatal predictors of persistent pulmonary hypertension (PPH) and the need for extracorporeal membrane oxygenation (ECMO) in fetuses with congenital diaphragmatic hernia (CDH). Methods: We performed a systematic literature review on antenatal diagnostic tests in fetuses with isolated CDH. The primary outcomes assessed were PPH within 28 days of age and the need for ECMO. Quality of studies was assessed with the QUADAS‐2 tool. Meta‐analysis was performed when at least three studies reported on the same test. Sensitivity analysis was performed according to prenatal management of CDH (tracheal occlusion vs expectant management). Results: Thirty‐eight studies met the inclusion criteria. Fifteen reported on the incidence of PPH only, 19 on the need for ECMO only and four reported on both outcomes. The general quality of the studies was moderate; most studies were retrospective (61%) and single‐center series (92%). One study included only fetuses undergoing tracheal occlusion, 22 included only fetuses managed expectantly in utero and 15 included both populations. We could not identify antenatal predictors of PPH. The need for ECMO was predicted by parameters indicative of lung size: lung‐to‐head ratio (LHR) (relative risk (RR) for LHR < 1, 1.65 (95% CI, 1.27–2.14)) and observed/expected LHR (standardized mean difference (SMD), –0.70 (95% CI, –0.98 to –0.42)) measured by ultrasound and observed/expected total lung volume (SMD, –1.00 (95% CI, –1.52 to –0.48)) measured by magnetic resonance imaging. Liver herniation was also associated with an increased risk of need for ECMO (RR, 3.04 (95% CI, 2.23–4.14)). These results were confirmed by a sensitivity analysis of studies that included only expectantly managed cases. Data on vascular assessment for the prediction of PPH could not be pooled as most of the parameters were evaluated in a single series or in different series by the same principal investigator. Conclusions: In fetuses with CDH, lung size and liver herniation predict the need for ECMO, however a predictor for PPH is still lacking. Further studies aimed at diagnosing impaired vascular development in utero should therefore be undertaken. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.